Tooth Organ Bioengineering: Cell Sources and Innovative Approaches - Hasan A. Jamal (MDPI AG, 2016)
Various treatment approaches for restoring missing teeth are being utilized nowadays by using artificial dental crowns/bridges or the use of dental implants. All aforementioned restorative modalities are considered to be the conventional way of treating such cases. Although these artificial therapies are commonly used for tooth loss rehabilitation, they are still less conservative, show less biocompatibility and fail to restore the natural biological and physiological function. Adding to that, they are considered to be costly due to the risk of failure and they also require regular maintenance. Regenerative dentistry is currently considered a novel therapeutic concept with high potential for a complete recovery of the natural function and esthetics of teeth. Biological-cell based dental therapies would involve replacement of teeth by using stem cells that will ultimately grow a bioengineered tooth, thereby restoring both the biological and physiological functions of the natural tooth, and are considered to be the ultimate goal in regenerative dentistry. In this review, various stem cell-based therapeutic approaches for tooth organ bioengineering will be discussed.